Os desafios da eficácia e o problema da evasão na formação técnica: um estudo sobre o IFSP Sertãozinho/SP - Frighetto, Fabiana Andréa Fracácio (Universidade Federal de São Carlos, 2018)
This work presents the problem of effectiveness in the activities developed by IFSP campus Sertãozinho from two analysis movements. In the first movement, it was intended to verify the effectiveness of the students' capacity for inclusion and qualified training, an important goal of the pedagogical projects and the mission of the Federal Institutes in the recent period, with the construction of the socioeconomic profile of the students from 2008 to 2016 in the various courses offered at the institution during the period. In the second movement, taking as a central element the permanence and conclusion of the course, it was attempted to map the size and causes of evasion in some courses of the institution (Mechanical Engineering - Baccalaureate modality, Technology in Human Resources Management - Technologist modality, Chemistry - Licenciatura modality, Chemistry Technician modality - Integrated, Technician in Administration - Concurrent / Subsequent modality and Technician in Mechanics - modality EJA). Besides the measurement of these two crucial points to evaluate the actions of the IFSP / Sertãozinho regarding the inclusion goal and the training goal, the work also presents a brief description of the history of technical education - upper and middle - in Brazil and the social and the region of insertion of the institution.
The challenges of effectiveness and the problem of avoidance in technical graduation: a study on the IFSP campus Sertaozinho/SP
Keywords: Formação técnica e profissional; Eficácia; Evasão e permanência; Technical and vocational training; Efficacy; Avoidance and permanence; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA